Goniometric measurement of joint angles in crab-eating foxes (Cerdocyon thous) - Castilho, Maíra Sales [UNESP]; Rahal, Sheila Canevese [UNESP]; Mesquita, Luciane Dos Reis [UNESP]; Neto, Ramiro Das Neves Dias [UNESP]; Conceição, Renato Tavares [UNESP]; Denes, Ana Luiza [UNESP]; Kano, Washington Takashi [UNESP]; Padovani, Carlos Roberto [UNESP]; Melchert, Alessandra [UNESP] (American Association of Zoo Veterinarians, 2018)
This study aimed to assess joint angle values in the forelimbs and hind limbs of crab-eating foxes (Cerdocyon thous) using a conventional manual goniometer. Nine captive crab-eating foxes, aged over 1 yr old, weighing from 5.9 to 7.5 kg were used. The maximum flexion and maximum extension of the shoulder, elbow, carpal, hip, stifle, and tarsal joints were measured. The range of motion was determined through the difference between the maximum flexion and the maximum extension. There was no significant difference between the right and left sides in the goniometric measurements. The mean values of the range of motion for shoulder, elbow, carpal, hip, stifle, and tarsal joints were respectively 108°, 99°, 131°, 79°, 103°, and 86°. The goniometric values of the crab-eating foxes can be used as means of comparison with other animals from the same species for diagnostic purposes, research documentation, and evaluation of therapeutic procedures.
Keywords: Canidae; Goniometry; Joint; Motion; Wild